Advances in point-of-care technologies with biosensors based on carbon nanotubes - Justino, Celine I. L.
Healthcare is the combination of diagnosis, treatment, and prevention of any disease in humans, which is being constantly improved with efficient, rapid, useful point-of-care (POC) technologies as molecular diagnostic devices. In this way, biosensors based on carbon nanotubes (CNTs) have been developed and used in recent years, due to their high sensitivity, specificity, rapidity in analysis, low cost, and ease of use. This review provides an up-to-date overview of the analytical performance of emerging technologies in the form of POC biosensors based on CNTs, which can be implemented in the clinical area, mainly for the detection of cancer biomarkers and glucose (analytes associated with two of the most common diseases in developed world, cancer and diabetes).This review also addresses the synthesis, the properties and the areas of application of CNTs and the characteristics and the clinical importance of POC testing.